PRACTICE OF INDEPENDENTLY ESTABLISHED STANDARDS FOR HIGHER EDUCATION AND PROGRAMS DEVELOPMENT AND APPLICATION - Nikolay N. Matushkin; Vladimir I. Freyman; Alexandr A. Yuzhakov; Alexander N. Danilov; Efim L. Kon; Nikolay V. Lobov (Высшее образование в России)
This article is about approaches and realization results of the self-setting educational standard with innovation orientation 210700 «Infocommunication technologies and networks» («master» degree) project designing. Structure of self-setting educational standard, requirements to the results and the conditions for realization of the basic professional educational programs with innovation oriented training are described. Self-setting educational standards ensure diversification of master programs with innovation orientation and systematic organization of learning process adjusted for regional business and industry.